Cost control in construction project of the site - Mohd Iskandar Zulkarnain, Talib (2010)
Cost control is an important issue in construction project management. It is widely practiced by contractors in Malaysia and needs to carry out throughout the life of a project. A brief interview with a class A contractor found out that the contractor lack the knowledge of cost control system. Hence, a study is carried out to study the cost control method in a construction project, to identify the cost control method frequently used by class A contractor during the construction stage and to identify the problem faced by the class A contractor in controlling the costs on site. The study is carried out in the district of Batu Pahat, Kuantan, and Muar. A total of 20 questionnaires were sent to the class A contractor and the data analyzed using the average index and frequency analysis. From the study, the main problem faced by the class A contractor are shortages of material, labor or mechanical plant, difficulty in collection of cost data, ever-changing environment of construction work, qualified expertise, duration of the project and additional costs to carry out the cost control system.